Modelling Of Extrinsic Fiber Optic Sagnac Ultrasound Interferometer Used For Displacement Measurements - Benhamida, S.; Rehouma, F. (University of Eloued جامعة الوادي, 2012)
Ultrasonic waves are used extensively in nondestructive testing both for characterization of material properties, in this paper, we describe a fiber optic sensor suitable for detection of ultrasonic waves. This sensor is based on an extrinsic fiber optic sagnac interferometer. The proposed sensor model can act as a conventional in-phase detector or as a narrowband detector. In this study we use methods interference of ultrasonic waves between the source of ultrasonic waves and the object under investigation is exploited. The main advantages of the proposed sensor are the ability to detect ultrasonic waves on the surface; this sensor possesses higher sensitivity and accuracy than the pulse method. The cavity resonator was very successfully used for measurement of small ultrasound velocity changes. The ultrasonic interferometric technique based on phase-locked loop is the most suitable for measurements of small displacements. This method ensures the highest sensitivity and accuracy.
Articale in Journal of fundamental and Applied Sciences Vol. 04 N. 01
Keywords: Laser-based ultrasonic, fiber optic sensor, Sagnac interferometer.